INTEGRATED MARKETING COMMUNICATION DALAM MENINGKATKAN IMAGE PADA UNIVERSITAS HINDU NEGERI I GUSTI BAGUS SUGRIWA - I Gusti Ayu Putri Trisnayanti; Ida Bagus Gede Candrawan; I Ketut Wardana Yasa (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2022)
Universitas Hindu Negeri (UHN) I Gusti Bagus Sugriwa Denpasar is one of the Hindu State Universities located in the urban area of Denpasar, namely North Denpasar, of course, it cannot be separated from the very fierce competition with universities in Bali, image restoration needs to be done to build an image, therefore universities must be able to market their institutions to the community so that they can arouse interest and then attract prospective students. One of them is by applying the concept of Integrated Marketing Communication (IMC). This research method uses a descriptive qualitative approach, and produce research namely Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar conducting marketing communication with the concept of IMC, namely advertising, personal selling, sales promotion, public relations, interactive marketing, and direct marketing, From the implementation, there are communication barriers, namely communication process barriers, physical, frame of mind, and technical barriers. IMC activities will certainly have implications for internal, external, marketing communications and social media.